PENGABDIAN MASYARAKAT BAGI KELOMPOK TANI KARYA DI DESA FATAATU KECAMATAN WEWARIA KABUPATEN ENDE - Mutiara, Charly; Bolly, Yovita Yasintha; Laga, Yulius (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2024)
Karya Mekar is a farmer group in Fataatu Village, Wewaria District, Ende Regency. This farmer group is a rice seed measuring group that participates in daily rice cultivation activities. The group, founded in 2010 and has 22 members, has various problems regarding rice cultivation and its group. The issues faced include a lack of knowledge of organic fertilizers, organic pesticides, pests on rice plants, group management, and marketing. These problems were increasingly felt by group members at the end of 2023 when the climate change phenomenon had a greater impact. The biggest impact of this phenomenon is that the rainy season changes, brown planthopper pests are increasingly attacking rice plants, plants die, production is low, and the price of grain and rice is increasingly expensive on the market but low at the farmer level. Community service activities have been carried out to overcome these problems. The purpose of this activity is to increase the knowledge of farmer group members and be able to efficiently overcome the difficulties experienced. This community service activity was carried out using the extension method, and to measure the success of the extension activity, a pre-test and post-test were carried out. The results of the pre-test and post-test were assessed by percentage and displayed in the form of a graph. Extension on organic fertilizers showed an increase in knowledge of members of the Karya Mekar farmer group by 93%, organic pesticide extension by 90.9%, pest extension on rice plants showed an increase in knowledge by 83.6%, group management extension 84.5% and marketing management extension 85.5%. The increase in group knowledge shows the success of the implementation of community service activities. The follow-up plan for the future is to make a demonstration plot location to practice all the knowledge that has been learned and the measurement of heavy metals in the soil and rice produced by group members.